MCSCF-MRMP2 and DFT Exploratory Study on the Stability of Possible Intermediates in the Ru(H2O)6 2+ + H2O2 Reaction: Importance of the Multiconfigurational Character in the Description of the Ru=O Moiety - Ana Elizabeth Torres (Journal of the Mexican Chemical Society, 2012)
MCSCF-MRMP2 and DFT calculations were performed in order to analyze the stability and geometrical parameters of some possible intermediates for the reactions Ru2+ + H2O2 and Ru(H2O)6 2+ + H2O2. At MCSCF-MRMP2 level of calculation, the stability predicted for the RuIVO(H2O)5 2+ suggests an energetic preference of the reaction Ru(H2O)6 2+ + H2O2 toward the products involving this high-valence intermediate, in agreement with the commonly accepted mechanism for this kind of reactions. Due to its multiconfigurational character, the DFT approaches used in this work exhibited some limitations for properly describing the RuOIV(H2O)5 2+ ion and therefore the energy gap between the possible investigated intermediates.